2020
DOI: 10.3389/fcell.2020.00850
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Is a Rising Star in Researches of Ocular Diseases

Abstract: A newly rediscovered subclass of noncoding RNAs, circular RNAs (circRNAs), is produced by a back-splicing mechanism with a covalently closed loop structure. They not only serve as the sponge for microRNAs (miRNAs) and proteins but also regulate gene expression and epigenetic modification, translate into peptides, and generate pseudogenes. Dysregulation of circRNA expression has opened a new chapter in the etiology of various human disorders, including cancer and cardiovascular, neurodegenerative, and ocular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 143 publications
(281 reference statements)
0
34
0
Order By: Relevance
“…Numerous studies have shown that circRNA plays an important role in the pathophysiological processes of various diseases, such as cancer and cardiovascular disease, and in the development of neurons. Furthermore, studies have shown that circRNA also affects the occurrence and development of fibrotic diseases of organs such as the heart, lungs, and kidneys, playing a key role in organ fibrosis ( 1 , 4 9 ). It has been shown that a member of the circRNA family, circHIPK3, is abnormally upregulated in organ fibrosis, cancer, and other diseases, suggesting that circHIPK3 is involved in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that circRNA plays an important role in the pathophysiological processes of various diseases, such as cancer and cardiovascular disease, and in the development of neurons. Furthermore, studies have shown that circRNA also affects the occurrence and development of fibrotic diseases of organs such as the heart, lungs, and kidneys, playing a key role in organ fibrosis ( 1 , 4 9 ). It has been shown that a member of the circRNA family, circHIPK3, is abnormally upregulated in organ fibrosis, cancer, and other diseases, suggesting that circHIPK3 is involved in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNAs have been manifested not to be the transcriptional noise, and but to be the important regulatory molecules ( Zhuang et al, 2015 ; Chen et al, 2016 , 2017 ; Li et al, 2016a , b ; Tran et al, 2020 ), and circRNAs are novel endogenous non-coding RNAs that have been identified as owing key regulatory roles in the cancer biology ( Ma et al, 2019 ; Di Agostino et al, 2020 ; Dong et al, 2020 ; Jin et al, 2020 ; Li and Wang, 2020 ; Liu et al, 2020 ; Ou et al, 2020 ; Zhang et al, 2020a ). circRNAs act as important roles in the development and progression of cancers and are involved in various biological processes, such as cell proliferation, apoptosis, and migration by regulating gene expression ( Liu et al, 2019 ; Di Agostino et al, 2020 ; Ji et al, 2020 ; Tang and Chen, 2020 ; Wang et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of SIK2 reversed malignant cervical carcinomas cells phenotypes promotion of overexpression circAMOTL1. Some studies illustrated that circRNAs and miRNAs could play important roles in cervical cancers ( Jayamohan et al, 2019 ; Dong et al, 2020 ; Jin et al, 2020 ; Li et al, 2020 ; Ou et al, 2020 ; Tang and Chen, 2020 ; Tran et al, 2020 ; Zhang et al, 2020a ). Previously, the function of circAMOTL1 in cervical cancers is completely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations